ANALISIS KETERKAITAN SIFAT TANAH DENGAN KANDUNGAN KARBON TANAH PADA HUTAN SEKUNDER, KELAPA SAWIT, AGROFORESTRI DAN SAWAH DI KABUPATEN LUWU TIMUR - karuru, sakti swarno; ., Hadija; Galla, Ernytha A. (Program Studi Kehutanan Universitas Muslim Maros, 2024)
This research aims to describe the relationship between soil properties and soil carbon content in secondary forests, oil palm, agroforestry and rice fields. Determination of soil sampling points is carried out at each land cover unit with fairly uniform vegetation conditions that represent the land cover. Soil samples were taken at 3 depth levels, namely 0-10 cm, 10-20 cm and 20-30 cm. There are two types of soil sampling carried out; disturbed land and intact land. The results of the research show that the ability of each land cover to have soil carbon value with the relationship between soil properties has different results. The highest soil carbon values in various land covers in East Luwu Regency are rice fields at 70.50 tons/ha, oil palm 59.38 tons/ha, agroforestry 58.13 tons/ha and secondary forest 54.60 tons/ha. The results of the C-organic correlation test were found to be a very influential parameter on paddy field cover, where the correlation value of C-Organic to soil carbon stocks was 0.998, showing significant correlation results at the 00.5 level with a very strong relationship.